Book review: Peter Flaschel and Sigrid Luchtenberg, Roads to Social Capitalism: Theory, Evidence, and Policy (Edward Elgar, Cheltenham, UK and Northampton, MA, USA 2012) 384 pages - Fritz Helmedag (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
More than 75 years ago, John Maynard Keynes wrote in his magnum opus: 'The outstanding faults of the economic society in which we live are its failure to provide for full employment and its arbitrary and inequitable distribution of wealth and incomes' (Keynes 1936 [1978]: 372). This statement still applies today and has gained even more significance in recent times. In contrast to all the grandiose promises which accompanied the march back to Manchester liberalism during the past decades, present-day capitalism performs rather poorly.
Keywords: 330